Preparative isolation of Heteroclitin D from Kadsurae Caulis using normal-phase flash chromatography - Xiao-Xue Yu; Qian-Wen Wang; Xin-Jun Xu; Wei-Jian Lv; Ming-Qian Zhao; Zhi-Kun Liang (Journal of Pharmaceutical Analysis, 2013)
Heteroclitin D (H.D) was successfully isolated from Kadsurae Caulis by using flash chromatography and recrystallized by methanol, 10.2 mg of H.D was obtained from 4.86 g of crude extract, and the purity determined by HPLC was 99.4%. The structure was identified by UV, IR, MS, and NMR analysis. The fast, simple and efficient method can be applied to the preparation of reference substance of H. D. Keywords: Kadsurae Caulis, Heteroclitin D, Normal-phase flash chromatography